Factors influencing intention to use e-banking: An integrated model approach - Cakerri, Lorena; Petanaj, Migena; Kosova, Robert (International Journal of Innovative Research and Scientific Studies, 2025)
The expansion of information technology presents significant challenges, making the development of technology-based banking services an inevitable trend in global economic integration. This study aims to develop and empirically evaluate a model to predict factors that influence customers’ behavioral intentions when utilizing electronic banking (e-banking) services. The proposed conceptual model is based on an expansion of the Unified Theory of Acceptance and Use of Technology (UTAUT) through the integration of two additional factors: assurance and customer support. Data were collected via an online questionnaire administered to 379 e-banking customers. Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Map Analysis (IPMA) were employed to assess the effects of various factors on the adoption and use of e-banking services in Albania. The findings of this study indicate that assurance and customer support are the most significant determinants of e-banking customers’ continuance intention. Based on these findings, managers should prioritize electronic service quality, as it plays a substantial role in influencing the acceptance of e-banking.